Student Confidence in Learning During the COVID-19 Pandemic: What Helped and What Hindered? - Guppy, Neil (Archīum Ateneo, 2023)
When COVID-19 struck, higher education scrambled. Teaching and learning swerved abruptly to emergency remote instruction. For many students, the rapid refashioning of courses of instruction meant suddenly confronting new, radically different learning scenarios. We know relatively little about what enabled or constrained students' confidence in their ability to learn as a consequence. Using questionnaire responses from undergraduate students (N = 3806) who were studying at nine different institutions in six different countries on four different continents, we examine factors that helped, and hindered, students' confidence in their learning ability. We investigate a range of factors, including technology, living circumstances, communications with professors and peers, course attributes, as well as personal student circumstances and characteristics. Our results demonstrate that communication, both with peers and professors, was especially associated with the confidence students expressed in their ability to learn under conditions of emergency remote instruction. Household living conditions and technology also were important correlates.